2023
DOI: 10.1002/aelm.202201091
|View full text |Cite
|
Sign up to set email alerts
|

Sb2Te3/MoS2 Van der Waals Junctions with High Thermal Stability and Low Contact Resistance

Abstract: Two‐dimensional transition metal dichalcogenides (TMDCs) demonstrate great potential in nanoelectronics devices owing to their high carrier mobility in the atomically thin channel regime. However, high contact resistance between source/drain electrodes and TMDC channels hinders the TMDCs applications in the very‐large‐scale integration (VLSI) field. Here, this work reports atomically aligned van der Waals (vdW) junction fabrications through thermal‐induced crystallization of layered Sb2Te3 electrodes on monola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Figure 5d presents the spectral photoresponse of the pristine MoS2 and AgNDs/MoS2 photodetectors. It is clearly determined that the responsivity of the AgNDs/MoS2 photodetector is superior to that of the counterpart MoS2 Thus far, in addition to topological insulators, many other metallic/semimetallic 2DLMs, such as graphene [130,131], graphite [132], reduced graphene oxide [133], 1T -WS 2 [134], TaSe 2 [135,136], ZrTe 2 [137], Sb 2 Te 3 [138], etc., have been validated as highly competitive self-passivated electrode building blocks. These 2DLMs have different work functions, providing rich choices for device design.…”
Section: Light Harvesting Enhancementmentioning
confidence: 99%
“…Figure 5d presents the spectral photoresponse of the pristine MoS2 and AgNDs/MoS2 photodetectors. It is clearly determined that the responsivity of the AgNDs/MoS2 photodetector is superior to that of the counterpart MoS2 Thus far, in addition to topological insulators, many other metallic/semimetallic 2DLMs, such as graphene [130,131], graphite [132], reduced graphene oxide [133], 1T -WS 2 [134], TaSe 2 [135,136], ZrTe 2 [137], Sb 2 Te 3 [138], etc., have been validated as highly competitive self-passivated electrode building blocks. These 2DLMs have different work functions, providing rich choices for device design.…”
Section: Light Harvesting Enhancementmentioning
confidence: 99%
“…In a previous study, we demonstrated the vdW stacking of antimony telluride (Sb 2 Te 3 ) on molybdenum disulfide (MoS 2 ), 16) and showed a substantial enhancement in the device performance of monolayer MoS 2 n-type FETs with Sb 2 Te 3 source/drain contacts, which was resulted from a significant reduction of contact resistance. This result suggests that the conduction band edges of Sb 2 Te 3 and MoS 2 are closely aligned.…”
mentioning
confidence: 99%